1986
DOI: 10.1063/1.97077
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characteristics of InAsSb/GaSb heterojunctions

Abstract: Heterojunctions of n-type InAs0.95Sb0.05 grown by metalorganic chemical vapor deposition on n-type GaSb substrates were studied by capacitance-voltage and current-voltage measurements. The n-n heterojunctions are strongly rectifying and behave like metal-(n) GaSb Schottky diodes with a barrier height of 0.80±0.02 eV. These measurements establish that the band lineup in this system is of the broken gap variety. We measure the valence-band offset, Ev(GaSb)−Ev(InAs0.95Sb0.05), to be 0.67±0.04 eV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…From Figure 3(a), it is observed that the device is showing rectifying characteristics, both in the dark (room temperature as well as low Epitaxytemperature) and under ultraviolet radiation, which are consistent with the n-n isotype heterojunctions of other materials as reported by others [81,82,105]. I-V characteristics were obtained on Al/InGaN/Si(111)/Al, Al/InGaN/Al, and Al/Si (111)/Al.…”
Section: Ingan/si Heterostructure-based Uv and Ir Photodetectorssupporting
confidence: 68%
See 1 more Smart Citation
“…From Figure 3(a), it is observed that the device is showing rectifying characteristics, both in the dark (room temperature as well as low Epitaxytemperature) and under ultraviolet radiation, which are consistent with the n-n isotype heterojunctions of other materials as reported by others [81,82,105]. I-V characteristics were obtained on Al/InGaN/Si(111)/Al, Al/InGaN/Al, and Al/Si (111)/Al.…”
Section: Ingan/si Heterostructure-based Uv and Ir Photodetectorssupporting
confidence: 68%
“…So far the most extensively studied material systems are ZnO/Si, In x Ga 1-x As, In x Ga 1-x Sb, Ge-Si, etc. [81,82]. Very few groups have reported studies on isotype heterojunctions of In x Ga 1Àx N system [83,84].…”
Section: Heterostructures Of Iii-nitride Semiconductors For Optical Amentioning
confidence: 99%
“…However, due to large effective mass of holes than electrons, their mobility is very less and thus a p-p isotype junction is not preferred for high speed electronic applications. So far, the most extensively studied material systems are ZnO/Si, 1,6 In x Ga 1Àx As, In x Ga 1Àx Sb, 7 Ge-Si, 2 etc. Very few groups have reported studies on isotype heterojunctions of In x Ga 1Àx N system.…”
Section: Introductionmentioning
confidence: 99%
“…First, the n-GaSb/n-InAsSb interface is staggered type II, resulting in an electron accumulation layer on the InAsSb side and depletion on the GaSb side. This results in a rectifying junction for low GaSb doping levels as has been previously reported [8]; however, for sufficiently high GaSb doping, it should become Ohmic due to tunneling. Comparison of the homojunction versus heterojunction band alignments in Fig.…”
Section: Resultsmentioning
confidence: 70%